How Far North Did the African Monsoon Fringe Expand During the African Humid Period? Insights From Southwest Moroccan Speleothems. Issue 23 (13th December 2019) - Sha, Lijuan; Ait Brahim, Yassine; Wassenburg, Jasper A.; Yin, Jianjun; Peros, Matthew; Cruz, Francisco W.; Cai, Yanjun; Li, Hanying; Du, Wenjing; Zhang, Haiwei; Edwards, R. Lawrence; Cheng, Hai
Abstract: We present new high‐resolution oxygen isotope (δ 18 O) records from three NW African speleothems located at 31°N. The present‐day rainfall patterns at 31°N in NW Africa are linked to negative winter North Atlantic Oscillation phases. However, on multimillennial time scales, our δ 18 O records, together with other hydroclimate records, provide new evidence of humid conditions during the mid‐Holocene, a period that was presumably characterized by arid climate. Thus, the apparent increase in moisture during the mid‐Holocene is interpreted better as an increase in summer rainfall. This is most likely linked to the expansion of the West African summer monsoon fringe during the African Humid Period, which terminated in our record abruptly around 4 Kyr BP. The temporospatial difference with speleothem records from N Morocco suggests that the High‐Atlas Mountains might have been a topographic barrier to further expansion of the West African summer monsoon fringe into higher latitudes. Plain Language Summary: The Holocene African Humid Period in North Africa, characterized by the expansion of vegetation into the Green Sahara, has been linked to the intensification of the West African summer monsoon (WASM). However, the temporospatial pattern of the African Humid Period, especially the northernmost expansion of the WASM, remain a matter of controversy, largely owing to the lack of precisely dated and high‐resolution paleoclimatic records. This study presents new high‐resolution paleoclimate data based on speleothem oxygen isotope records from a key site at 31°N in NW Africa. Our data suggest that the WASM expanded to 31°N in NW Africa during the mid‐Holocene and terminated abruptly at 4 Kyr BP. Key Points: Holocene rainfall variability in NW Africa is inferred from precisely dated and high‐resolution speleothem δ 18 O records The West African summer monsoon expanded to 31°N in NW Africa during the mid‐Holocene The African Humid Period ended with an abrupt interval of megadrought around 4 Kyr BP in NW Africa